Human Resource Management in Islamic Schools - Kasiman, Kasiman; Warisno, Andi; Anshori, M Afif; Andari, An An (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
The goal of this study is to identify trends in the administration of human resources (HR) in integrated Islamic schools (SIT). This study employs collecting books on research objects as qualitative descriptive technique. The results state that qualifications, recruitment strategies, staff orientation, pay policies, employee regulations, coaching and development, employee evaluation, career and employee ranks, and welfare are just a few of the tasks that make up human resource management in an integrated Islamic school. All staff members who participate in the Integrated Islamic School are required to successfully complete each of these management processes.